Hydrogen sulphide detection by CMOS integrated tungsten oxide nanowire networks. (2017) - Krainer, Johanna; Deluca, Marco; Lackner, Eva; Wimmer-Teubenbacher, Robert; Sosada, Florentyna; Gspan, Christian; Rohracher, Karl; Wachmann, Ewald; Köck, Anton
Abstract: Metal oxide nanostructures like tungsten oxide nanowires are intensively studied materials for sensor applications. In this work we report on tungsten oxide gas sensors integrated on a CMOS fabricated microhotplate chip. Tungsten oxide gas sensors were prepared by drop coating of a nanowire network suspension onto interdigitated electrodes prefabricated on the CMOS microhotplate chip. The tungsten oxide nanowire network was characterised by TEM and Raman spectroscopy, confirming their non-stoichiometric state. Using tungsten oxide nanowire networks as gas sensing material we observed high sensitivity to hydrogen sulphide: concentrations of 1 ppm have been detected with a sensor response up to 55%.